Integrated system for the production of fuel-cell grade H2 from bioethanol (2021)
ABSTRACT: A lab-scale prototype of a bioethanol fuel processor unit to produce H2 suitable for high CO-tolerant fuel cells was developed in this Thesis. To this end, a system that couples bioethanol reforming to produce syngas and the CO removal from the syngas produced in the reformer was designed. Initially, the system was evaluated using powder catalysts in both modules of the fuel processor unit (i.e., the bioethanol reformer and the reactor for CO removal), focusing on selecting an appropriate AuCu-based catalyst to carry out CO removal from an actual syngas in a single catalytic unit. The effect of the Au/Cu ratio and the support on the catalytic performance in CO removal was studied. It was found that an AuCu catalyst with a weight ratio of Au/Cu = 1 supported on polyhedral nanoparticles of CeO2 favors a balance between activity, selectivity and stability, ensuring a CO conversion. > 96%. Afterwards, catalysts structured on monoliths were evaluated for each module of the fuel processor unit. So, syngas was produced over monoliths washcoated with RhPt/CeO2- SiO2, which were evaluated with actual bioethanol (i.e., obtained from sugarcane press). The bioethanol reformer ensured a continuous production for 120 h of a syngas with an H2 content > 60%. Similarly, monoliths washcoated with AuCu catalysts were used for the CO removal, seeking to develop a compact and economical system to connect to the bioethanol reformer. It was identified that a monolith coated with an AuCu catalyst supported on a mixed oxide of CeO2-SiO2 (with molar ratio Si/Ce = 3) favors the production of a suitable gas (i.e., with a concentration of CO < 5%) to be fed to a high temperature proton exchange membrane fuel cell. Finally, the results of the catalytic evaluations were used as a starting point to build a scaled prototype to produce H2 from bioethanol obtained from residual biomass. The prototype had a cost of US$53,000, where 24% corresponds to the bioethanol reformer, 31% correspond to the unit to remove the CO, and the rest was ascribed to auxiliary equipment. The results of This thesis seek to contribute to the implementation of unconventional technologies associated with H2 in the Colombian agroindustry sector.